The Effect of Good Corporate Governance on Firm Value with Financial Performance As an Intervening Variable - Agustina Dian Putri Manurung (International Publisher (YAPENBI), 2022)
The purpose of this study was to analyze the effect of Good Corporate Governance on company value with financial performance as an intervening variable in property and real estate companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Sampling in this study used purposive sampling, so that a total of 50 data samples were obtained (10 companies x 5 years). The type of data used is secondary data taken using documentation. The data analysis technique used is multiple linear regression analysis and path analysis. The results of the research show that managerial ownership has no effect on financial performance. Meanwhile, institutional ownership influences financial performance. Managerial ownership and institutional ownership have no effect on firm value. Meanwhile, financial performance influences firm value. And based on path analysis using the Sobel test, financial performance cannot mediate the effect of managerial ownership on firm value. However, financial performance is able to mediate the effect of institutional ownership on firm value